(3Cef GdbGQI GdChQHjI aj GdSjGSI GdNGQLjI GdCeQjcjI HYO fgGjI GdMQH GdHGQOI (B/s - (3HhYeGeI, RgjQs ((3YfGHI, GdLRGFQ (B:s (3HjQhJ (B:s (3OGQ GdhSGe GdYQHj ddfTQ hGdJhRjY ;s (3ecJHI Rjf GdMbhbjI hGdCOHjI,s, 2011)
(3gPG GdcJGH OQGSI JHMK aj Cge MdbGJ GdgfOSI GdCefjI GdLOjOI GdJj CQGOJ hGTfWf(B-(3HYO fgGjI GdMQH GdHGQOI(B-(3Cf JHfj ef NdGdgG fXGeG YHQ bGQj jeJO ef aGfchaQ Edi adGOjahSJhc hjTed cGed GdbGQI GdChQhHjI(B. (3ZOGI fgGjI GdMQH GdHGQOI cGf GdeWdhH ef bGOI CeQjcG JMed egeI djSJ SgdI OGFeG ; ELJQGM WQjb hSW HjFI ZjQ eSJcTaI HGdeQI BedG aj GdhUhd Edi hLgI de Jcf hGVMI JeGeG efP GdHOGjI, hEdi MO eG CcKQ JYbjOG ef HjFI GdMQH GdHGQOI, Cbd bGHdjI ddJbOjQ hCbd bGHdjI ddJMce, dG JXgQ gPg GdegeI GdLOjOI MjfgG HTcd CcKQ hVhMG ef XghQgG aj ChQhHG, aaj bdH QhjJge GdTGedI JXgQ EQGOI GdCeQjcjjf aj GdJYGed eY VeGf Cef GdbGQI GdChQhHjI cgOa ESJQGJjLj ZjQ bGHd ddJMhd(B. (3Ef NjGQ GdhdGjGJ GdeJMOI(B-(3aj YgO EOGQI GdQFjS cdjfJhf JMOjOG(B-(3GdbGVj HEHbGA EdJRGegG hGdMaGX Ydi hLhOgG aj GdfXGe GdLjhSJQGJjLj GdPj jeKdg fXGe Cef ChQhHG HYO fgGjI GdMQH GdHGQOI, dG jecf JaSjQg EdG HGdESJfGO Edi JMdjd jHQR EYJHGQGJ ESJQGJjLjI JNVY dUjQhQI JGQjNjI dG JJYdb aj GdeWdb HGdMQH GdHGQOI, hHGdJGdj agj JJLGhR JOGYjGJ fgGjJgG hJJcja eY eSJLOGJ YGde de jYO jTHg cKjQG YGdegG(B. (3dbO YedJ GdSjGSI GdNGQLjI GdCeQjcjI aj gPg GdeQMdI Ydi EYGOI JCSjS GdQGHWI YHQ GdCWdSjI ef NdGd EYGOI HfGA YdGbI LjhSjGSjI eJLOOI eHfjI Ydi eHOC GdbjGOI GdPj jbJVj Cf JeJdc GdbhI GdeJahbI eTQhYjI LeY GdBNQjf aj efXheI LeGYjI, hMb GdeHGOQI hGdSjQ Hge fMh ZGjGJ eTJQcI, eY GdSeGM dge hOaYge Edi dYH COhGQ TQGcI(B-(3jJMedhf CYHGFgG(B-(3Jba YfO NW QaV cd MQcjI bO JDOj Edi JgOjO hVY GdJahb hecGfI GdQjGOI(B.s
(3edGMb (B: (3UaMI (B585-680.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B681-736.s
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: (3GdCef Gdbhejs -- (3ChQhHGs; (3ChQhHGs -- (3YdGbGJ NGQLjIs -- (3GdhdGjGJ GdeJMOI GdCeQjcjIs; (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3YdGbGJ NGQLjIs -- (3ChQhHGs